The Aversion Function of the Limbic Dopaminergic Neurons and Their Roles in Functional Neurological Disorders - Zhengming He (Frontiers in Cell and Developmental Biology, 2021)
The Freudian theory of conversion suggested that the major symptoms of functional neurological disorders (FNDs) are due to internal conflicts at motivation, especially at the sex drive or libido. FND patients might behave properly at rewarding situations, but they do not know how to behave at aversive situations. Sex drive is the major source of dopamine (DA) release in the limbic area; however, the neural mechanism involved in FND is not clear. Dopaminergic (DAergic) neurons have been shown to play a key role in processing motivation-related information. Recently, DAergic neurons are found to be involved in reward-related prediction error, as well as the prediction of aversive information. Therefore, it is suggested that DA might change the rewarding reactions to aversive reactions at internal conflicts of FND. So DAergic neurons in the limbic areas might induce two major motivational functions: reward and aversion at internal conflicts. This article reviewed the recent advances on studies about DAergic neurons involved in aversive stimulus processing at internal conflicts and summarizes several neural pathways, including four limbic system brain regions, which are involved in the processing of aversion. Then the article discussed the vital function of these neural circuits in addictive behavior, depression treatment, and FNDs. In all, this review provided a prospect for future research on the aversion function of limbic system DA neurons and the therapy of FNDs.